Improvement of Water Quality of Koranorya Water Supply System-Mbarara Municipality. - Nabaasa, Gorden (Kabale University, 2023)
This report provides an enhanced design aimed at improving the water quality of koranorya community-kakiika division-mbarara municipality where by the water quality enhancement components have been designed basing on preliminary studies and laboratory water quality tests plus a precise and comprehensive study of the existing literature on aspects such as water sources which include rain water, surface water, ground water and possible causes of contamination, water quality parameters which include microbiological, chemical and physical parameters, plus the water treatment processes which basically include pre-treatment, storage, pre-settlement, pre- filtration, aeration, chemical coagulation, filtration and disinfection processes. The preliminary studies as indicated in this report include the map study, the detailed study and the household survey whereby the map study aided in figuring out the exact location of the area of interest and the water source, the detailed survey helped to identify the abstraction point, treatment processes at the current water treatment plant, public perception on the current water quality and the house hold survey to obtain the necessary water demand since the study mainly considered the domestic supply. The laboratory water quality tests were conducted at the South Western Umbrella of Water and sanitation and the certificate has been included in this report In addition to the above, the photographs for some of the activities carried out within the course of this project have also been included in this report.